Climate and Environmental Risk Management in the Banking Sector : A Focus on Agriculture in Czechia - Sosnytska, Alina; Houska, Daniel; Tomčiak, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
Sustainable development depends on healthy ecosystems; however, climate change and environmental degradation pose significant risks to businesses and financial systems. The agricultural sector is particularly vulnerable to climate and environmental (C&E) risks due to its substantial climate and nature-related impacts and dependencies. Consequently, financial institutions may face heightened credit risk driven by C&E transition and physical risks associated with agricultural lending. Yet, the banking sector lacks detailed guidance for assessing natural capital credit risk in agriculture, a challenge further complicated by the significant variation in material risks across agricultural sectors and regions. This thesis investigates climate and environmental risks that are likely to be material in credit risk assessments within the agricultural sector in Czechia. It identifies primary climate and nature-related impact and dependency risk drivers that may lead to transition or physical risks and opportunities. Ultimately, the thesis proposes strategies for mitigating C&E risks through effective risk management practices, sustainable investments, and procedural improvements. Key implementation challenges include the complexity and interconnectivity of natural capital processes, technological barriers and costs, and the need for a coordinated climate-nature transition within agriculture and the banking sector.
Vedoucí práce: Daniel Houska
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses